Surfactant-Polymer Coreflood Simulation and Uncertainty Analysis Derived from Laboratory Study - Hakiki, Farizal; Maharsi, Dara Ayuda; Marhaendrajana, Taufan (Journal of Engineering and Technological Sciences, 2015)
This paper presents a numerical simulation study on coreflood scale derived from a laboratory study conducted on light oil and water-wet sandstone samples from fields at Tempino and Kenali Asam, Sumatra, Indonesia. A rigorous laboratory study prompted a specified surfactant type among dozens of screened samples, i.e. AN3NS and AN2NS-M for Kenali Asam and Tempino, respectively. The coreflood scale numerical simulation study was performed using a commercial simulator, on the basis of the results from the laboratory study, at a constant temperature of 68Â°C, 0.3 cc/min injection rate and under 120 psia confining pressure. To get better recovery, the cores were tested using surfactant and polymer in a blended mode, containing 0.03% w/w polymer diluted in each field brine, which accommodated around 8000 ppm salinity. The most significant variable in the multiphase flow is the relative permeability curve, which is affected by interfacial tension (IFT) during waterflooding and surfactant-polymer (SP) flooding. This study shows that relative permeability will be shifted at ultra-low IFT (10-3 to 10-4 mN/m). This shifting phenomenon is governed by the interpolation parameter set, which implicitly represents the capillary number. Further work in matching the numerical results to the coreflood was conducted by changing the interpolation parameters.